Neutrophil-to-lymphocyte ratio as a prognostic biomarker for patients with locally advanced esophageal squamous cell carcinoma treated with definitive chemoradiotherapy - Zhou, Xi-Lei (Sci Rep, 2017)
The present study evaluated the clinical and prognostic value of neutrophil-to-lymphocyte ratio (NLR) in patients with locally advanced esophageal squamous cell carcinoma (ESCC) treated with definitive chemoradiotherapy (dCRT). A total of 517 patients with ESCC were enrolled and analysed retrospectively. The NLR was calculated at three time points: baseline, post-treatment, and at the time of tumor progression. Elevated NLR was defined as a ratio ≥5. High NLR at baseline was present in 204 (39%) patients and was significantly correlated with larger tumour size, advanced TNM stage, worse ECOG performance status, and dCRT response (p < 0.05). At a median follow-up of 17 months, patients with higher NLR at baseline had poorer progression-free survival (PFS) and overall survival (OS). On multivariate analysis, elevated NLR at baseline was independently associated with PFS and OS (HR = 1.529, p < 0.001 for PFS; HR = 1.856, p < 0.001 for OS). In addition, patients with high pre- and post-treatment NLR demonstrated worse clinical outcomes than other groups. Our results suggest that NLR is an independent prognostic indicator for patients with ESCC undergoing dCRT and changes in NLR level with treatment may indicate therapeutic benefit.